IMPACT OF THE WAR ON THE ENERGY SYSTEM OF UKRAINE - CHORNII, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the state of the energy sector of Ukraine in the pre-war period and the current period. The state of development of the energy industry in the period 2016-2021 was determined, which made it possible to outline the main positive trends and negative phenomena during this period. The state of the energy industry is established, taking into account the damage and loss of capacities located in the temporarily occupied territories. On the basis of the established patterns of development of the industry, strategic priorities for the development of the energy market with European countries were determined based on the principles of synchronization of energy systems. In order to establish appropriate cooperation, the measures that must be implemented by the government of the country in order to achieve the established goal were outlined. The necessity of restructuring and changing the functioning of the state's energy market to ensure its autonomy and the development of fair competition was proven. Measures to support and develop the energy industry using the principles of green energy are proposed.
Keywords: energy system; war; Ukraine